Product Quality and Brand Image as Drivers of Repeat Purchase Decisions: Kualitas Produk dan Citra Merek sebagai Faktor Penentu Keputusan Pembelian Ulang - Alfin Rizki Bagus Permadi; Minto Waluyo (Academia Open, 2025)
General Background: Rapid technological advancements have transformed consumer behavior, especially in the smartphone industry, where performance, design, and innovation are key competitive aspects. Specific Background: Samsung, as a leading smartphone brand, continuously enhances its product quality and brand image to sustain customer loyalty, particularly with flagship models such as the Galaxy S25 Ultra. Knowledge Gap: Despite extensive studies on purchasing behavior, limited research integrates product quality, brand image, and purchase decisions as mediating factors influencing repurchase intention in premium smartphone contexts. Aims: This study investigates the effect of product quality and brand image on repurchase intention, mediated by purchase decision, among Samsung Galaxy S25 Ultra users in Indonesia. Results: Using Structural Equation Modeling (SEM) with AMOS on 100 respondents, findings reveal that brand image significantly influences purchase decision and repurchase intention, while product quality significantly impacts repurchase but not purchase decision. Purchase decision does not mediate the relationship effectively. Novelty: The integration of SEM-based mediation analysis provides a comprehensive understanding of causal relationships among variables in digital-era consumer behavior. Implications: Strengthening brand perception and maintaining consistent product quality are essential strategies for fostering long-term customer loyalty in competitive smartphone markets. Highlights: Brand image significantly drives both purchase and repurchase behavior. Product quality impacts repurchase but not initial purchase decisions. Purchase decision shows weak mediation between quality, image, and repurchase. Keywords: Product Quality, Brand Image, Purchase Decision, Repurchase Intention, SEM-AMOS